Decreased activation along the dorsal visual pathway after a 3-month treatment with Galantamine in mild Alzheimer's disease - HAMPEL, HARALD; BOKDE, ARUN LAWRENCE WARREN (Wolters Kluwer, 2009)
Visual perception has been shown to be altered in Alzheimer?s disease (AD) patients and it is associated with decreased cognitive function. Galantamine is an active cholinergic agent, which has been shown to lead to improved cognition in mild to moderate AD patients. This study examined brain activation in a group of mild AD patients after a 3 month open-label treatment with galantamine. The objective was to examine the changes in brain activation due to treatment. There were two tasks to visual perception. The first task was a face matching task to test the activation along the ventral visual pathway and the second task was a location matching task, to test neuronal function along the dorsal pathway. Brain activation was measured using functional magnetic resonance imaging. There were 5 mild AD patients in the study. There were no differences in task performance and in the cognitive scores of the CERAD battery before and after treatment. In the location matching task, we found a statistically significant decrease in activation along the dorsal visual pathway after galantamine treatment. A previous study found that AD patients had higher activation in the location matching task compared to healthy controls. There were no differences in activation for the face matching task after treatment. Our data indicate that treatment with galantamine leads to more efficient visual processing of stimuli or changes the compensatory mechanism in the AD patients. A visual perception task recruiting the dorsal visual system may be useful as a biomarker of treatment effects.
PUBLISHED
Keywords: Psychiatry; neurodegeneration; Alzheimer?s disease